2016
DOI: 10.1107/s2053229616005441
|View full text |Cite
|
Sign up to set email alerts
|

Transferred multipolar atom model for 10β,17β-dihydroxy-17α-methylestr-4-en-3-one dihydrate obtained from the biotransformation of methyloestrenolone

Abstract: Biotransformation is the structural modification of compounds using enzymes as the catalysts and it plays a key role in the synthesis of pharmaceutically important compounds. 10β,17β-Dihydroxy-17α-methylestr-4-en-3-one dihydrate, C19H28O3·2H2O, was obtained from the fungal biotransformation of methyloestrenolone. The structure was refined using the classical independent atom model (IAM) and a transferred multipolar atom model using the ELMAM2 database. The results from the two refinements have been compared. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Several databases have been constructed, such as the Invariom database (Dittrich, Hü bschle et al, 2006), UBDB (Dominiak et al, 2007), ELMAM (Zarychta et al, 2007) and its improved version ELMAM2 (Domagała et al, 2012). Several studies have exploited the aspherical atom databases in routine crystallographic modelling (Jelsch et al, 1998(Jelsch et al, , 2005Dittrich et al, 2005Dittrich et al, , 2007Dittrich et al, , 2008Dittrich et al, , 2009Dittrich, Strumpel et al, 2006;Volkov et al, 2007;Zarychta et al, 2007;Bąk et al, 2009;Faroque et al, 2016Faroque et al, , 2018Shahid et al, 2018) and have successfully shown that the application of the method results in a notably improved molecular geometry, superior refinement statistics, a better description of the thermal motion and an improvement of phases. Furthermore, on the basis of transferred electrondensity parameters, a number of electron-density-derived properties, like electrostatic potential, dipole moment and the topological properties of covalent and noncovalent interactions, can be closely estimated quantitatively.…”
Section: Introductionmentioning
confidence: 99%
“…Several databases have been constructed, such as the Invariom database (Dittrich, Hü bschle et al, 2006), UBDB (Dominiak et al, 2007), ELMAM (Zarychta et al, 2007) and its improved version ELMAM2 (Domagała et al, 2012). Several studies have exploited the aspherical atom databases in routine crystallographic modelling (Jelsch et al, 1998(Jelsch et al, , 2005Dittrich et al, 2005Dittrich et al, , 2007Dittrich et al, , 2008Dittrich et al, , 2009Dittrich, Strumpel et al, 2006;Volkov et al, 2007;Zarychta et al, 2007;Bąk et al, 2009;Faroque et al, 2016Faroque et al, , 2018Shahid et al, 2018) and have successfully shown that the application of the method results in a notably improved molecular geometry, superior refinement statistics, a better description of the thermal motion and an improvement of phases. Furthermore, on the basis of transferred electrondensity parameters, a number of electron-density-derived properties, like electrostatic potential, dipole moment and the topological properties of covalent and noncovalent interactions, can be closely estimated quantitatively.…”
Section: Introductionmentioning
confidence: 99%